Desain Pembelajaran PAI di Era Society 5.0 - Astuti, Nita Yuli (IQRO: Journal of Islamic Education, 2024)
In this industrial era 5.0, PAI learning requires that it can innovate in the learning process. As a teacher, you can design and revitalize the previous traditional learning system into more modern learning in three ways, namely Discruptive Mindset, Reshape or create and self driving. In addition, teachers can also formulate goals, determine learning strategies and determine the use of learning media in accordance with this 5.0 era. Good learning objectives refer to the ABCD formula, namely (Audience, Behavior, Condition, and Degree). These steps make it easier for teachers to develop learning objectives. For the use of learning applications in the 5.0 era that can be used such as Skype and Zoom, Google Meet, Discord, Gsuite for Edu (Google Suite for Education) Edmodo, Kahoot and the Ministry of Education and Culture established a learning house online. In addition, there are many more applications that PAI teachers can use to support learning in this 5.0 era. The strategies that can be used are inquiry strategies, participatory strategies, strategies, blended learning, discovery learning strategies.